Caging the beast : a theory of sensory consciousness - Droege, Paula (Advances in consciousness research, 2003)
"Caging the Beast: A Theory of Sensory Consciousness offers to explain what these conscious sensory states have in common, by virtue of being conscious as opposed to unconscious states. After arguing against accounts of consciousness in terms of higher-order representation of mental states, the theory claims that sensory consciousness is a special way we have of representing the world. The book also introduces a way of thinking about subjectivity as separate and more fundamental than consciousness, and considers how this foundational notion can be developed into more elaborate varieties. An appendix reviews the connection between consciousness and attention with an eye toward providing a neuropsychological instantiation of the proposed theory."--Jacket